Variações nos usos da língua falada: reflexões a partir de atendimento fonoaudiológico em grupo com adolescentes e adultos - Falcão, Ana Regina Graner (2021)
Introduction: Although the linguistic variations do not correspond to communication disorders, the disputes and social asymmetries manifested by the valuation of language variations, are a source of linguistic prejudice and social discrimination, reaching processes of "pathologization". In our study, a certain number of speakers of non-prestigious linguistic variations, assuming some speech disorder, sought the health service with a complaint of suffering discrimination due to linguistic prejudice. They experienced since repeated sensation of inferiority, social withdrawal in certain environments, even lowering of self-esteem; dimensions that can take, according to the reports, leading to bouts of anxiety or depressive episodes. Objective: The objective of the research was to analyze the repercussions of linguistic variations in a group of subjects made up of young people and adults, seeking to, establish indications for reflection on this problem in the field of health, especially in the management of these repercussions in the field of speech therapy. Method: From the point of view of the method, the research has a descriptive nature and characterized, in it's design, as a case study. The 'Focus Group Discussion' methodology was used, which consists in favoring and promoting the construction of a group discourse on a certain issue; group discourse which will be the object of the research. Results: The results and their discussion show that the linguistic variations of the research subjects are constituted in function of origin, socio-cultural extraction and socioeconomic condition and were perceived as a significant variable of discrimination and social exclusion, whose reiteration made them believe it was a matter of health or personal limitation. The analytical categories inferred from the focus group: prejudice and bullying; the speech community and social exclusion; expectations in relation to the prestigious norm. The Speech therapy work should: - recognize and value the suffering of victims, denaturalizing ideas and values that assume linguistic variations as "deviations", mitigating the "pathologization" linked to the idea of linguistic variation as speech disorder and/or cognition; - promote the transit through linguistic variations, understanding phonetic-phonological, syntactic, semantic and prosodic nuances, evaluating the uses and social contexts of oral discourse genders. Conclusion: It concludes with the establishment of indications to speech therapy to welcome and assist the victims of linguistic prejudice, in the scope of the clinical action of prevention and health promotion